Advertisement call of Rhinella inopina Vaz-Silva, Valdujo & Pombal, 2012 (Anura: Bufonidae) from the type-locality, northeastern Goiás State, Central Brazil - de Andrade, Sheila Pereira; Rocha, Cezar Filho; Victor-Junior, Edmar Pereira; Vaz-Silva, Wilian (Zootaxa, 2015)
The Rhinella crucifer species group currently comprises six species of toads: R. abei (Baldissera, Caramaschi & Haddad, 2004); R. crucifer (Wied-Neuwied, 1821); R. henseli (A. Lutz, 1934); R. ornata (Spix, 1824); R. pombali (Baldissera, Caramaschi & Haddad, 2004); and, R. inopina Vaz-Silva, Valdujo & Pombal, 2012. Recent genetic studies suggest five species in the R. crucifer species group and show evidence of hybridization between R. crucifer and R. ornata (Thomé et al. 2012).